The Concept of "Time" as the Ideological Foundation of Cultural Identity - A. A. Koroleva (Vestnik MGIMO-Universiteta)
The author considers time as a universal category of human cognition. Cultural identity is closely linked with the conceptual view of the world. On the example of phraseology in the Russian and Spanish are considered cultural and national peculiarities of perception of time.